Managing an invasive tree in coastal dunes: The importance of follow-up treatments to improve the recovery of protected habitats - Duarte, Liliana Neto; Marchante, Elizabete; Marchante, Hélia (Frontiers in Environmental Science, 2023)
Conservation of biodiversity in Protected Areas is often threatened by invasive alien plants (IAP) and its successful management requires proper planning, resources, and monitoring to adjust future interventions. Although follow-up controls and the evaluation of different management actions through monitoring programs are crucial in an adaptive management strategy, they are often neglected. Acacia longifolia is one of the most widespread IAPs in the Portuguese coastal areas, causing several negative impacts. This study reports the results of different control methods of A. longifolia in two forest plantations over coastal dunes in two protected sites in Portugal, under different management regimes, for over four years. The best results were achieved after hand-pulling, but due to its high costs this method is not suitable for large areas. Cut treatments, including the use of brush hogs, brush cutters, and chainsaws, resulted in variable A. longifolia stumps resprout. Follow-up treatments, whether mechanical and/ or chemical, reduced the number of A. longifolia resprouts, kept its cover below 20% and height below 50 cm. Furthermore, control with brush cutters/ hogs reduced the seed bank of A. longifolia by 74%, and control with disc harrow allowed an even greater reduction (91%). In areas where no follow-up treatments were carried out, A. longifolia started producing flowers two and a half years after the initial treatment, restarting the cycle of seed production. Nevertheless, a biological control agent that reduces A. longifolia seed production (Trichilogaster acaciaelongifoliae) is established and spreading in the controlled areas, suggesting that new seed production by these plants will be soon controlled. Although seldom represented, with the reduction of A. longifolia it is expected that more species characteristic of the protected habitats will start to emerge. Our results stress the importance of persistence of follow-up treatments if higher success in IAPs control is to be achieved, not only due to the resprouting ability of many species (despite this is not very high in A. longifolia), but also when invasive plants can produce extensive persistent seed banks. The role of management regime on the level of success in controlling IAP will be discussed.